Dynamic centrifuge tests of concrete dam. - Uchita, Y.
Dynamic tests of a concrete gravity dam are, for the first time, performed inside a centrifuge. Details of the experimental procedure, data interpretation, and results are presented. It is shown (in conjunction with a parallel paper) that these tests cannot only provide a direct assessment of certain aspects of dam safety, but more importantly provide a data base for possible non-linear finite element code validation.
Keywords: Dams; Earthquake; Centrifuge